Quality by Design Approach for Optimization of Diclofenac Sodium-Loaded Liposomes Using Design of Experiments - Dermawan, Doni; Steven; Hiendrawan, Stevanus; Tjandrawinata, Raymond R. (MPI (Media Pharmaceutica Indonesiana), 2026)
This study aimed to screen and optimize the critical process variables that significantly influence the preparation process of diclofenac sodium (DS)-loaded liposome using a quality by design (QbD) systematic approach. In this study, Plackett-Burman screening design (PBD) was employed to screen the most significant process and formulation variables. Further optimization of DS-loaded liposomes was done using Response Surface Method-Central Composite design (RSM-CCD). DS-loaded liposomes were formulated using the thin-film hydration method. The particle size (PS) and encapsulation efficiency (EE), as the key to liposome drug product qualities, were defined and evaluated. Differential scanning calorimetry (DSC) spectrum, in vitro drug release profile, and stability study were also investigated. The results showed that particle size and encapsulation efficiency of the optimum formulation were 146.60 nm and 79.77% with high coefficient of determination values of 0.9989 and 0.9984, respectively. The study showed that PBD could be useful to screen the most significant variables, and RSM-CCD could be employed to study surfaces and to locate the optimal response to achieve maximized EE and minimized PS.